2022
DOI: 10.31849/dinamisia.v6i4.10382
|View full text |Cite
|
Sign up to set email alerts
|

E-kiosk dan Pelatihan Konten Digital Instagram untuk Peningkatan Layanan Kesehatan Klinik

Abstract: The public health index is part of the Regional Government's plan, also the Sustainable Development Goal number 3. To assist public health improvement, a community service was carried out with partner Citra Sehat Clinic, Sadang Serang, Bandung City. The activity was carried out through preparation, implementation, and evaluation. The preparation stage was conducted through surveys, observations, literature collection, and interviews. The implementation phase consisted of installing furniture and tools, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…There are three phases of activities in the implementation of community service activities, namely the preparation phase, the implementation phase, and the evaluation phase (Wulandari et al, 2022). Meanwhile, Rahmawati et al (2021) revealed four stages of community assistance, which consist of the discussion stage with residents, observation, planning, and implementation.…”
Section: Methodsmentioning
confidence: 99%
“…There are three phases of activities in the implementation of community service activities, namely the preparation phase, the implementation phase, and the evaluation phase (Wulandari et al, 2022). Meanwhile, Rahmawati et al (2021) revealed four stages of community assistance, which consist of the discussion stage with residents, observation, planning, and implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Karena promosi melalui media sosial terkait erat dengan pemasaran digital, prinsip-prinsip penting dalam content writing dan copywriting 'penulisan konten dan penulisan iklan' diterapkan dalam pembuatan media promosi untuk Balaiyanpus DPAD DIY. Pelatihan pembuatan konten digital untuk peningkatan layanan kesehatan sebuah klinik (Wulandari et al, 2022) bisa menjadi contoh dan acuan. Demikian juga dengan pelatihan Copywriting untuk pemasaran online di Instagram untuk sebuah kantor yang melayani jasa pengurusan visa (Santika et al, 2023).…”
Section: Pembahasanunclassified
“…Untuk memperluas pasar produk yang dihasilkan oleh anggota KIM NAS dan/atau warga, kegiatan-kegiatan pelatihan desain grafis dan pembuatan konten digital juga penting (Desnelita et al, 2019;Nasution & Hasan, 2019;Wulandari et al, 2022). Pelatihan terkait pengemasan produk juga diperlukan agar lebih menarik konsumen (Sutarti et al, 2023).…”
Section: Hasil Pembahasan Dan Dampakunclassified